Proceso jurídico de constitución del observatorio de comercio exterior e inversión extranjera - Bejarano, Ileana J. (2019)
The present titration work consists of a value proposal for the legal constitution of the Observatory of Foreign Trade and Foreign Investment of the University of Otavalo, which will serve as a tool for the generation of research and training of the different economic actors of the N Zone. ° 1 of Ecuador. First, the background and function of the observatories is briefly considered, in order to continue with the definition of the different regulations that validate the constitution of the present observatory in Ecuador. Therefore, the Constitution of the Republic of Ecuador 2008, the Organic Law of Citizen Participation and the Organic Law of the Council of Citizen Participation are taken as legal basis. The same that allow us to give a pass to the elaboration of the proposal of creation of the observatory from which the act of conformation of the observatory is born as the only document that validates its legal constitution within the University of Otavalo.